Revisiting the surface anatomy of the sciatic nerve in the gluteal region. Issue 1 (8th August 2014) - Currin, Stephen S.; Mirjalili, S. Ali; Meikle, Grant; Stringer, Mark D.
<x xml:space="preserve">Abstract</x> The surface anatomy of the sciatic nerve (SN) in the gluteal region is clinically important (e.g., intramuscular injection). Anatomy texts describe the nerve in relation to the posterior superior iliac spine (PSIS), ischial tuberosity (IT), and greater trochanter (GT) but descriptions are inconsistent. The surface anatomy of the SN was determined in relation to these bony landmarks using computed tomography (CT) scans in living adults. One hundred consecutive adult pelvic CT scans (36 females, mean age 76 years) were available for dual consensus analysis. A further 19 adults (9 females, mean age 74 years) underwent pelvic CT scans in both prone and supine positions. The surface projection of the SN along a line between the PSIS and IT and between the IT and GT was measured. The SN was identified in 95% of scans at a mean of 5.2 ± 1.0 cm from the PSIS and 11.4 ± 1.1 cm from the IT. The SN was a mean of 5.8 ± 0.8 cm from the IT and 6.2 ± 1.0 cm from the GT. There were no significant differences in mean positions of the nerve between sides and sexes. A small but clinically irrelevant difference in the surface marking of the SN was found between supine and prone positions with respect to the GT and IT but not in relation to the PSIS and IT. In living adults, the SN lies approximately one‐third of the way along a line between the PSIS and IT and half way between the GT and IT. Clin. Anat. 28:144–149, 2015. © 2014 Wiley Periodicals, Inc.